2021
DOI: 10.1371/journal.pone.0247771
|View full text |Cite
|
Sign up to set email alerts
|

Is there meaningful influence from situational and environmental factors on the physical and technical activity of elite football players? Evidence from the data of 5 consecutive seasons of the German Bundesliga

Abstract: The study aimed to identify the effects of situational (match location, match outcome and strength of team/opponent team) and environmental (ambient temperature, relative humidity, WBGT, ground and weather condition) factors on the physical and technical activity of elite football on individual playing positions. Physical and technical activity were collected from 779 football players competing in the German Bundesliga during 5 domestic seasons, from 2014/2015 to 2018/2019, totalling 1530 matches. The data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 65 publications
1
31
1
1
Order By: Relevance
“…Previous studies which have investigated the RP without the context of the ball possession have reported that RPs vary according to playing positions due the different tactical roles during the soccer match [8,10,13,39]. Similarly, the present study analysed the RP in the context of the ball possession and found significant differences among playing positions in the RP during both the AP (i.e., when the team has the ball in their possession) and DP (i.e., when the opponent has the ball in their possession) of the game.…”
Section: Difference Among Playing Positions In the Rps In The Ap And Dp Of The Gamementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies which have investigated the RP without the context of the ball possession have reported that RPs vary according to playing positions due the different tactical roles during the soccer match [8,10,13,39]. Similarly, the present study analysed the RP in the context of the ball possession and found significant differences among playing positions in the RP during both the AP (i.e., when the team has the ball in their possession) and DP (i.e., when the opponent has the ball in their possession) of the game.…”
Section: Difference Among Playing Positions In the Rps In The Ap And Dp Of The Gamementioning
confidence: 99%
“…Previous studies have demonstrated that players regularly transit between brief bouts of high-intensity running and longer periods of low-intensity running [1,7]. These performances can be affected by different factors, such as the player's playing position in the game [8][9][10], physical capacities [7,11,12], tactical formations [13,14] and technical level [15]. In addition, contextual variables, such as the match status (win, draw, lose), location (home, away) and opponents' level (top, middle, bottom), impact the RP [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, using tracking systems to monitor match demands has become a hot topic of research, referring to work rate, activity profile or match running performance [5,9,11,12]. Several studies quantified the match running performance across national professional leagues, such as the English [13][14][15][16][17][18][19][20][21], Italian [3,22,23], Spanish [19,[24][25][26], French [20,27,28], German [29][30][31][32], Brazilian [33,34], Norwegian [35,36], Danish [37] and Australian leagues [38,39]. The literature also focused on the European Champions League [40][41][42][43][44], UEFA Cup/Europe League [41,44] and the World Cup [45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Physical performance in football is commonly analyzed by quantifying the match running performance (MRP), which includes the total distance covered, distances covered in various speed zones, and acceleration rates [5][6][7][8][9][10]. For example, it is well known that football players can cover between 9 and 14 km, performing 0.7-3.9 km of high-speed distance and 0.2-0.6 km of sprint distance, with ~600 accelerations, during matches [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%